Comparison of Biomechanical Models for Roundhouse Kicking in Skilled Martial Arts Students of Taekwondo and Wushu (Sanda) - Mahdi Najafian Razavi; Meysam Rezaei (Islamic Azad University, Hamedan Branch, 2023)
Objective Participation in martial arts such as Karate, Taekwondo, Kung Fu, and Wushu has increased recently, and it is possible that determining the difference between performing different kicks in skilled athletes can be of great help to coaches and beginner athletes for better performance and prevention of sports injuries. Methods Twelve athletes in two fields of Taekwondo and Wushu were divided into groups of six people. A motion analysis device was used to measure the variables of roundhouse kicking with the foot. Paired t-tests were used to analyze the data at a significance level of 0.05 for statistical analysis. Results Findings showed that there is no significant difference between the duration of the kicking (leg return), the maximum speed of the foot until the moment of kicking, the speed of the foot at the moment of strike, the angle of the knee at the moment of strike, and thigh internal rotation angle (p>0.05). However, significant differences were observed in the variables of maximum knee angle in the flexion axis, hip flexion angle at the moment of strike, lateral angle (Y&Z) of the thigh at the moment of strike, the amount of internal rotation of the hip (in terms of angle), the amount of lateral rotation to the outside of the hip, the maximum amount of internal angular changes of the thigh in terms of time, and maximum amount of hip lateral angular changes in terms of time (p<0.05). Conclusion According to the obtained results, it seems that there is a difference between some kinematic variables of rotational kicking in Taekwondo and Wushu disciplines, which is probably due to the type of kicks in Taekwondo and Wushu, as each of these sports probably requires different techniques.